Experimental investigation on vortex-induced force of a flexible pipe under oscillatory flow. (September 2022) - Zhang, Mengmeng; Fu, Shixiao; Ren, Haojie; Xu, Yuwang; Qin, Xu
Abstract: In this paper, vortex-induced force (VIF) characteristics of a flexible pipe under oscillatory flow are experimentally investigated with different KC numbers ranging from 10 to 178, and reduced velocities from 4 to 7.9. The strain information caused by vortex-induced vibration (VIV) at different cross-sections on the flexible cylinder is measured in the model test. Combined with the modal superposition method and inverse analysis method for hydrodynamic force, the hydrodynamic forces on the flexible cylinder are inverted, including the excitation force in phase with velocity and added mass force in phase with acceleration. Then, through a least square method with forgetting factors, the excitation coefficients and added mass coefficients at each time step are identified. The results show that the VIV excitation coefficient of a flexible pipe under oscillatory flow has a significant "acceleration and deceleration" effect, that is, the excitation coefficients are mostly positive at the acceleration section of the oscillatory flow and negative at the deceleration section. This "acceleration and deceleration" effect also explains the response amplitude modulation feature of VIV under oscillatory flow. And this effect can be represented by the dimensionless acceleration parameter γ of the flow field, and the range of γ corresponding to the positive excitation coefficient is affected by the KC number and the maximum reduced velocity. In addition, the added mass coefficients present different time-varying features under oscillatory flow with different maximum reduced velocity. When the maximum reduced velocity is larger than 6.5, the time-varying trend of the added mass coefficient is opposite to that of the flow velocity. While when the maximum reduced velocity is smaller than 6.5, the added mass coefficient is maintained around 2.0 in VIV excitation region; and it is around 1.0 in the non-excited region which is close to the added mass coefficient of a cylinder in still water.